Environmental Marine Geoscience 2. Multibeam Bathymetry and Backscatter Imaging of the Canadian Continental Shelf - Courtney, R.; Shaw, J. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2000)
Summary High-resolution, multibeam technology has revolutionized the study of marine continental shelf geology in the 1990s. For the first time, complete coverage maps of the seabed are becoming available: the marine equivalent of the aerial photograph. This article reviews the principles that lie behind multibeam bathymétrie and back scatter surveying, and also details the mapping platforms available to researchers in Canada. Examples of imagery derived from a widerange of geologic settings, spanning the Cambro-Ordovician through to the present, are presented from sites located on the eastern Canadian continental shelf.